Antiandrogens in the treatment of violent sexual behavior: ethical reflections - Sgreccia, Elio; Mele, Vincenza (Medicina e Morale, 1990)
A comprehensive and general treatment of sexological therapies considered from an ethical point of view does not yet exist, just as there is no agreement among the various schools on the most appropriate therapies for individual disorders or specific pathologies of sexuality.